2017
DOI: 10.3389/fpls.2016.01960
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Induced Glume Closure Resulted in Lower Fertility in Hybrid Rice Seed Production

Abstract: Predicted climate changes, in particular, the increased dimension and frequency of heat waves, are expected to affect crop growth in the future seriously. Hybrid rice relies on seed production from male sterile and restorer lines. Experiments were conducted over two consecutive years to compare the high temperature tolerance of parents of different hybrid rice combinations, in terms of fertility rate, flowering pattern, pollination and physiological parameters of the lodicule. Three male sterile lines and a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Therefore, we infer that the WAS is a critical period for the lodicules. An overview of the pathways for proteome metabolic changes in lodicules Many substances regulate the osmotic pressure of lodicules, such as soluble sugar (Zee & O'Brien, 1971;Wang, Gu & Gao, 1991;Yan et al, 2017), starch (Pissarek, 1971), calcium (Qin, Yang & Zhao, 2005;Chen et al, 2016) and potassium (Heslop-Harrison & Heslop-Harrison, 1996;Chen et al, 2016;Liu et al, 2017). Our findings, together with those of previous studies, provide an overview of the metabolic pathways involving the carbohydrates that regulate the osmotic pressure of the lodicules.…”
Section: Cleistogamy Provides Structural Barriers For Diseases Of Fussupporting
confidence: 61%
“…Therefore, we infer that the WAS is a critical period for the lodicules. An overview of the pathways for proteome metabolic changes in lodicules Many substances regulate the osmotic pressure of lodicules, such as soluble sugar (Zee & O'Brien, 1971;Wang, Gu & Gao, 1991;Yan et al, 2017), starch (Pissarek, 1971), calcium (Qin, Yang & Zhao, 2005;Chen et al, 2016) and potassium (Heslop-Harrison & Heslop-Harrison, 1996;Chen et al, 2016;Liu et al, 2017). Our findings, together with those of previous studies, provide an overview of the metabolic pathways involving the carbohydrates that regulate the osmotic pressure of the lodicules.…”
Section: Cleistogamy Provides Structural Barriers For Diseases Of Fussupporting
confidence: 61%
“…Shorter grain filling durations caused by high temperatures were due to the loss of sink activity owing to earlier senescence of the panicle (Kim et al, 2011). Previous studies have indicated that an increase in spikelet sterility caused by high-temperature stress was caused by abnormal anther dehiscence (Matsui and Omasa, 2002), glume closure (Yan et al, 2017) and impaired pollination (Matsui et al, 2005) and pollen germination (Jagadish et al, 2009). In the Yangtze Valley, Tian et al (2009) observed that a maximum temperature of approximately 35°C or daily mean temperature of 30°C (with relative humidity of approximately 70% and low wind speeds) lasting for more than 3 days during the flowering period, led to significant seed-set losses in rice plants.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the major goals for rice breeder to develop HS resistant cultivar [ 15 , 16 ]. It has been suggested that rice resistance to HS is a quantitative trait [ 17 ].…”
Section: Introductionmentioning
confidence: 99%